Pengaruh Literasi Keuangan, Persepsi Resiko, dan Motivasi Investasi terhadap Keputusan Investasi Mahasiswa di Galeri Investasi FEB Universitas Pembangunan Nasional Veteran Jawa Timur - Pradipta, Imron Maulana; YYuniningsih, Yuniningsih (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Investment is a financial instrument used to generate profits within a certain period of time. However, like any other financial activity, investment also involves risk, so it should be done by carefully considering the risks and potential benefits. To be able to consider risks and potential profits in investment maturely, an investor must have financial literacy and good risk perception of the investment instrument he will choose. This study aims to analyze the factors that influence investment decisions. This study used a sample of 66 respondents with Structural Equation Model (SEM) analysis. The results showed that financial literacy and financial motivation had a significant positive effect on investment decisions, while risk perception did not affect investment decisions. Keywords : Financial Literacy, Risk Perception, Investment Motivation, Investment Decisions.